Jaringan Pengelolaan Sampah Rumah Tangga sebagai Bentuk Transisi Ekonomi Sirkular di Kota Surabaya - Aida Fitri Larasati; Eko Budi Santoso (School of Postgraduate Studies, Diponegoro Univer, 2024)
Waste management in Surabaya City is part of a circular economy, various types of waste are processed into something that has a higher selling value and can drive the community's economy, both at the producer and consumer levels. This study explores how the flow of waste management takes place, both informally and formally. Through qualitative analysis in the form of social networks. The analysis visualizes the pattern of relations between actors and measures the centrality of each key actor. This analysis also helps researchers reveal that the criteria for social networks in waste management in the study area have the characteristics of transactional relationships and collaborative relationships with different patterns. In addition, the relational network looks different for the types of organic and inorganic waste, the highest complexity is found in the transactional network relationships for inorganic waste. Key actors, such as waste banks and scrap dealers, can connect massive collection points and waste management. In addition, researchers found that various parties have contributed significantly to realizing the circular economy transition. In collaboration relations, the Environmental Service has the main role as a regulator bridging the private sector, waste banks, and Non-Governmental Organizations (NGOs). The Main Waste Bank and the Nol Sampah Community have a role in encouraging changes in the community's paradigm to sort and manage waste with a different approach. In addition, the MSMEs and the informal sector have a significant role in transactional relations, forced by economic factors that can increase the recycling business field. The study findings also answer that household waste has been processed using the 3R concept (Reduce, Reuse, Recycle), part of the circular economy process. The potential for a circular economy transition can also be increased through various social approaches to increase cooperation and create more up-to-date innovations in waste management.